Rotavirus-specific neutralization assay enables evaluation of mucosal immune responses - Harzer, Maxi; Rückner, Antje; Vahlenkamp, Thomas W. (Frontiers in Immunology, 2025)
Mucosal infections are a major global health concern in humans and animals. Neutralization assays are considered the gold standard for evaluating functional antibodies but are typically limited to serum analysis. This often excludes mucosal sample types such as saliva or intestinal mucus, which may better reflect local immunity, particularly for enteric pathogens such as Rotaviruses (RV). We optimized and standardized a virus neutralization assay (VNA) for RVA to evaluate its applicability across serum, intestinal mucus, and saliva samples. Five key protocol variables were systematically assessed: (i) the applied trypsin concentration, (ii) the incubation time for proteolytic activation of the RV, (iii) the infection dose applied, (iv) the duration of neutralization time and (v) sample-specific factors that affect assay performance. The following parameters have proven to be optimal: (i) end concentration of 20 µg/ml Trypsin (ii) two hours for proteolytic activation of the RV, (iii) MOI of 0.5 – 3.0 x 10-3, (iv) two or eight hours of neutralization time for serum or saliva and mucus samples. Optimization of trypsin concentration and virus activation time significantly improved assay reproducibility across sample types. Analysis of the three validated sample materials of individual swine demonstrate that RV-specific neutralizing antibodies can be reliably detected in saliva. Saliva-based neutralization titers strongly correlated with those from intestinal mucus, indicating that salivary antibodies may serve as a non-invasive surrogate for gut mucosal immunity. The optimized VNA enables robust detection of mucosal neutralizing antibodies in saliva and intestinal mucus, offering a standardized, scalable approach for evaluating mucosal immune responses following RV infection or vaccination. This platform holds promise for broader application in mucosal immunology and vaccine monitoring, although its applicability in low-resource and pediatric settings still needs to be demonstrated.